STUDI TENTANG FAKTOR PENENTU MINAT BERKUNJUNG KE DESTINASI WISATA RELIGI - Pascoal Augusto De Carvalho Pinto; Setiyaningrum, Ari (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2025)
This research aims to analyze the influence of religious motivation, spiritual belief, place attachment, destination image, and country image on visit intention at religious tourism destinations. Apart from that, this research also tests whether destination familiarity is able to moderate the influence of religious motivation, spiritual belief, place attachment, destination image, and country image on visit intention at religious tourism destinations. The religious tourism destination studied was the Christ the King statue in the city of Dili, Timor-Leste. Primary data was collected through a survey by distributing questionnaires to 219 people who knew about the religious tourist destination of the Christ the King Statue in the city of Dili but had never come to visit it. Sampling used the purposive sampling method. The results of analysis using SEM-PLS indicated that religious motivation, place attachment, and country image have an influence on visit intention. Spiritual beliefs and destination image were found to have no influence on visit intention. The results of the moderation test show that destination familiarity does not moderate the influence of religious motivation, spiritual belief, place attachment, destination image, and country image on visit intention at religious tourism destinations.